CFD study of Savonius wind turbine: 3D model validation and parametric analysis. (May 2017) - Ferrari, G.; Federici, D.; Schito, P.; Inzoli, F.; Mereu, R.
Abstract: A CFD study is conducted in order to characterize the dynamic behavior of a Savonius vertical axis wind turbine. All simulations are executed using the open source code, OpenFOAM. Both two-dimensional and full three-dimensional cases have been investigated in order to provide a suitable tool for geometrical optimization of this rotor. Unsteady simulations are carried out at different tip speed ratio (TSR), varying angular speed of rotor at constant wind speed, using different one and two-equation URANS turbulence models and selecting the k − ω SST for the final analysis. The two-dimensional model was compared with experimental data available in literature and obtained from tests in wind tunnel. This simplified model shows an over-estimation of experimental data, reporting a maximum efficiency at TSR 1, 20% higher than experimental value. The results of 3D model are in good agreement with experiments with a peak of 0.202 at TSR 0.8 for a rotor with aspect ratio 1.1. The influence of the rotor height has been evaluated on flow dynamics of the turbine and its power coefficient. Highlights: CFD study to characterise the dynamic behaviour of a Savonius vertical axis wind turbine. URANS modeling approach with k-ω SST turbulence model in OpenFOAM code. Analysis at different TSR and angular speed of rotor at constant wind speed. Over-estimation of experimental data with 2D approach, good agreement with 3D approach. Evaluation of influence of the rotor height on fluid dynamics and power coefficient.